Accuracy of transthoracic echocardiography in diagnosis of cardiac myxoma - Kačar, Polona (Radiology and oncology (Ljubljana), 2025)
Background: The differential diagnosis of cardiac myxomas (CM), the most common benign primary cardiac tumors, is broad and a thorough diagnostic workup is required to establish accurate diagnosis prior to surgical resection. Transthoracic echocardiography (TTE) is usually the first imaging modality used for diagnosis of suspected CM. In a single tertiary centre study, we sought to determine the accuracy, sensitivity, and specificity of TTE in the diagnosis of CM and to determine echocardiographic characteristics indicative of CM. Patients and methods: We retrospectively analyzed clinical, echocardiographic, and pathohistological findings of 73 patients consecutively admitted for suspected CM. Results: After diagnostic workup, 53 (73%) patients were treated surgically at our institution. Based on preoperative TTE, patients were divided into a CM group (n=45, 85%) and non-myxoma (NM) group. Of the 53 pathohistological specimens obtained during surgery, 39 (73%) were CM. The sensitivity and specificity of preoperative echocardiography were 97% and 50%, respectively. The overall accuracy was 85%. All NM tumors were found in an atypical location and 72% of CM were found in a typical position in the left atrium (p < 0.001). Tumors in NM group were significantly smaller than CM (24.3 ± 13.2 mm vs. 37.9 ± 18.3 mm, p = 0.017). Conclusions: Our study confirms very good accuracy of TTE in the diagnosis of CM. The most important echocardiographic characteristics to differentiate between CM and tumors of different etiology are tumor location and size. Smaller tumors presenting at an atypical location are less likely to be diagnosed as CM, and these require additional imaging modalities for accurate diagnosis.
Keywords: cardiac mass; cardiac myxoma; cardiovascular imaging; echocardiography